Analysis of the Virtual Reality User Experience Improvement Through Human Vision Adjustment Using Diopter Dial - Sungeun Park; Wooksung Kim; Jihyung Kim (IEEE Access)
The head-mounted display (HMD) form factor is an essential element that influences the various emotions users experience during their virtual reality (VR) sessions. In particular, it has been announced that the VR experience highly depends on the user’s field of vision because it blocks the user’s view of the real world and transmits information exclusively in the virtual world. Users with eye diseases wore vision aids to experience VR environments or used them without sufficient vision. Furthermore, this problem led to factors that reduced the user’s sense of immersion and ease of use. In this paper, we analyzed how providing users with adjusted human vision via diopter dial affects the improvement of VR user experiences. The experimental procedure consisted of 2D video and 360-degree video as audiovisual content, as well as sitting mode games and room-scale mode games as playable content. We measured the immersion and sickness of the experimental environment using each verified questionnaire on the 5-point Likert scale and the discomfort score for each experimental content to measure the degree of discomfort. The experimental environment is Phase 1, where users experienced VR while wearing vision aids, and Phase 2, where users experience VR with human vision adjustment using a diopter dial without vision aids. The difference between the evaluation results of both experimental environments was 1.56 for immersion, 2.35 for sickness, and 3.85 for discomfort. Additionally, user feedback was gathered through in-depth interviews to enhance the reliability of the statistical analysis. Through these results, we confirmed that human vision adjustment using the diopter dial provides users with an improved form factor, reduces discomfort and sickness, and enhances the immersive feeling of the VR environment through improved display visibility.